Phobia of COVID-19 on people who aged 18 and older - ZORLU, MEHMET; ZORLU, MEHMET; Kiskac, Nese; KISKAÇ, MUHARREM; KISKAÇ, MUHARREM (My University, 2021)
Objectives: Our aim was to evaluate the participants with the COVID-19 scale in order to see the effects of the COVID-19 pandemic on people, which has affected the whole world along with our country, to be able to take the necessary precautions for the current pandemic and similar pandemics and to minimize the negative aspects globally. Methods: A total of 1010 people who aged 18 and older (between the ages of 18-76) were included in the research. Besides from the personal information of people who aged 18 and older such as a city of residence, age, gender, profession, education, the number of people who live in the same house, their chronic illnesses, marital status, and the existence of a child, a 20-question phobia of COVID-19 scale was carried out. The results were 95% reliable, and their significance was evaluated to be on p<0.05 level. Result: The COVID-19 Phobia Scale point for women was 54.97±14.44 while it was 51.28±14.06 for men, and between the two groups, there is a high level of significant difference (p<0.05) statistically, COVID-19 Phobia Scale point of people who have chronic illnesses is 56.51±15.84, meanwhile, the point of people who have no chronic illnesses was found to be 52.96±13.99, and it was detected that this difference was statistically significant (p<0.05). Conclusion: Besides the COVID-19 pandemic affecting the whole society, we see that the women population and people who have chronic illnesses are going through much more fear and anxiety.
Keywords: COVID-19; Pandemic; Phobia